A Comparative Analysis of Selected Improved Biomass Cookstoves’ Temperature Profiles Using the Testo 310 Flue Gas Analyzer - Lahai, Umar Museheeh; Ofosu, Eric Antwi; Gyamfi, Samuel (New Energy Exploitation and Application, 2025)
One of the major challenges facing the energy sectors in practically all developing countries worldwide is clean cooking. In Sierra Leone, only 1% of the population has access to clean cooking, making it one of the worst among the developing countries with clean cooking problems. Many people are switching to improved biomass cookstoves (IBCs), but the unprecedented production of charcoal‑based IBCs and varied designs, particularly ceramic linings, make it difficult for users to choose the right size. The study surveyed major IBC production and sales centres in Sierra Leone’s western regions between 2021 and 2023, examining temperature profiles of the metal stove (MS) and wonder stove (WS). The data showed that an average of 3352 MS and 1833 WS were produced and sold between 2021 to 2023. A water boiling test was adopted for IBCs testing and Testo 310 flue gas analyzer was used to track the temperature profiles of the chosen IBCs. The findings suggest that WS could be able to generate and retain heat more quickly and sustainably than MS. Additionally, the recorded temperatures and timings of all IBCs were also subjected to a systematic correlational analysis. A simulation of the various temperatures and times was also plotted to ascertain the temperature‑time graph differences. These results are relevant and could aid in the analysis of IBC emissions and thermal efficiency. Thus, the results of the study could be utilized to offer policy recommendations for IBC production and sales centres in Sierra Leone and other developing countries.